Influence of aggregate gradation on permanent deformation - Salgado Barra, Breno (2025)
The study evaluates the mechanical behavior of dense asphalt mixtures through laboratory permanent deformation tests conducted at 60 °C and a frequency of 1 Hz, using slabs compacted with a pneumatic compaction table. To compare the asphalt mixtures, aggregates sourced from the Amazon region (State of Pará) were used, along with petroleum asphalt cement (CAP 50/60) supplied by the Lubricants and Petroleum Derivatives Refinery of the Northeast (LUBNOR). The mixtures compared featured gradations within the limits of Band C defined by the National Department of Transport Infrastructure (DNIT), and gradation curves developed using the Fuller or Talbot equation, referred to as the practical curve (PC) and theoretical curve (TC), respectively. The findings indicate more satisfactory results for the theoretical curves when compared to the practical curve commonly used in the Amazon region.